Pengelolaan Pariwisata Tirta Taman Mumbul Sebagai Wisata Spiritual Di Desa Sangeh - Ni Luh Debby Krisnantari; Gusti Ngurah Made Suarga; Ida Ayu Made Dwi Astuti; Kharisma Subhan; I Gusti Ayu Made Wartini; Enik Aryani; Luh Rai Widiastuti; Ilham Hadi; Ni Luh Ayu Meytarini; Ni Luh Made Cencen Tunjung Sari; Luh Riniti Rahayu; I Wayan Astawa (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
This research uses qualitative research methods to explore and analyze the marketing mix of Tirta Taman Mumbul as spiritual tourism in Sangeh Village, Badung Regency. The research method involves in-depth interviews with relevant stakeholders, direct observation, and content analysis from secondary sources.The research results highlight the importance of the cultural and spiritual characteristics of the Tirta Taman Mumbul location in developing marketing strategies. Market segmentation is based on tourists' preferences and spiritual motivations. The uniqueness of this destination and the spiritual experiences it offers are the main focus in designing the marketing mix.In the context of tourism competition in Bali, research findings emphasize the need for a differentiation strategy that reflects the authenticity and spiritual values of Tirta Taman Mumbul. The quality of service and infrastructure is identified as an important element to strengthen a destination's attractiveness.This research also highlights the importance of including sustainability aspects in the marketing mix to reflect responsibility towards the environment and local culture.Thus, this research concludes that a qualitative approach is able to provide in-depth insight in designing a marketing mix that is in accordance with the characteristics and spiritual values of Tirta Taman Mumbul, increasing its attractiveness as a unique spiritual tourism destination in Badung Regency.